Kiplinger's the complete job search organizer [soundrecording] - O'Brien, Jack 1936-; Kiplinger Washington Editors (Los Angeles, Calif. Dove Audio, 1996)
A guide that helps you develop your job campaign strategy and get the job that melts your criteria.
Abridged.
Read by Mario Machado.
Keywords: Job hunting; Personality development; Psychology